The Effect of Organizational Culture and Organizational Political Perception on Employee Performance through Job Satisfaction as a Mediation Variable at PT "X" - Agdesuri, Syahadatan Beva; Erdiansyah, Rezi (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to analyze organizational culture's influence and political perception on employee performance, with job satisfaction as a mediating variable. The study was conducted on PT "X" employees using a quantitative approach. Data was collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method. The research sample consisted of 105 employees at PT "X", which was obtained through purposive sampling techniques. This study analyzes the influence of Organizational Culture (BO) and Organizational Political Perception (PPO) on Employee Performance (KK), with Job Satisfaction (KPK) as a mediating variable. The results showed that BO had a significant positive effect on the KK and the KPK, while the KPK did not have a significant effect on the KK. PPO has a significant positive effect on the KK, but not the KPK. The mediation route through the KPK is also insignificant in the relationship between BO, PPO, and KK. These findings emphasize the importance of a strong organizational culture and proper management of political perceptions in improving employee performance.